Public health response to the silent reintroduction of wild poliovirus to Israel, 2013–2014. (1st December 2016) - Moran-Gilad, J.; Kaliner, E.; Gdalevich, M.; Grotto, I.
Abstract: During 2013/14, Israel witnessed the silent reintroduction and sustained transmission of wild poliovirus type 1 (WPV1) detected through routine environmental surveillance performed on sewage samples. The public health response to silent poliovirus transmission in a population with high inactivated polio vaccine (IPV) coverage poses an emerging challenge towards the 'End Game' of global poliovirus eradication. This paper reviews the risk assessment, risk management and risk communication aspects of this poliovirus incident. Special emphasis is placed on the use of scientific data generated in the risk assessment phase to inform the public health response. Reintroducing a live vaccine in supplemental immunization activities in response to transmission of WPV or vaccine-derived poliovirus should be considered close to the 'End Game' of polio eradication, especially if targeting the population at risk is feasible. Such circumstances require a comprehensive contingency plan that will support the generation of important public health evidence at the risk assessment stage, thereby allowing to tailor the risk management approaches and underpin appropriate risk communication.